Evaluation of educational content of YouTube videos relating to neurogenic bladder and intermittent catheterization - Ho, Matthew; Stothers, Lynn; Lazare, Darren; Tsang, Brian; Macnab, Andrew (Canadian Urological Association Journal, 2015)
Introduction: Many patients conduct internet searches to manage their own health problems, to decide if they need professional help, and to corroborate information given in a clinical encounter. Good information can improve patients’ understanding of their condition and their self-efficacy. Patients with spinal cord injury (SCI) featuring neurogenic bladder (NB) require knowledge and skills related to their condition and need for intermittent catheterization (IC). Methods: Information quality was evaluated in videos accessed via YouTube relating to NB and IC using search terms “neurogenic bladder intermittent catheter” and “spinal cord injury intermittent catheter.” Video content was independently rated by 3 investigators using criteria based on European Urological Association (EAU) guidelines and established clinical practice. Results: In total, 71 videos met the inclusion criteria. Of these, 12 (17%) addressed IC and 50 (70%) contained information on NB. The remaining videos met inclusion criteria, but did not contain information relevant to either IC or NB. Analysis indicated poor overall quality of information, with some videos with information contradictory to EAU guidelines for IC. High-quality videos were randomly distributed by YouTube. IC videos featuring a healthcare narrator scored significantly higher than patient-narrated videos, but not higher than videos with a merchant narrator. About half of the videos contained commercial content. Conclusions: Some good-quality educational videos about NB and IC are available on YouTube, but most are poor. The videos deemed good quality were not prominently ranked by the YouTube search algorithm, consequently user access is less likely. Study limitations include the limit of 50 videos per category and the use of a de novo rating tool. Information quality in videos with healthcare narrators was not higher than in those featuring merchant narrators. Better material is required to improve patients’ understanding of their condition.